Ordinances and By-Laws of the Borough of Naugatuck 3 (1907) - (:unkn) unknown (My University, 1901)
Section 2-An Ordinance or By-Law Relating to Public Safety, Clauses 1-8: Prohibited the discharge of any pistol, revolver, gun, cannon, or other firearm, or air gun in any street, park, or public ground. Also prohibited the carry of any firearm, brass or metal knuckles, slung shot, or similar weapon with permission from the Warden.
Keywords: DISCHARGE